2015
DOI: 10.1016/j.ijmecsci.2013.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of high frequency vibro-impact drilling

Abstract: Modelling of the vibro-impact drilling system is undertaken in this study, and the results of the numerical analysis and comparison between two selected models are presented. The first one is a newly developed model of an existing experimental rig (three masses model) and the second one is a simplified low dimensional model (Pavlovskaia et al., 2001 [22]) created to describe the dynamic interaction between the drill-bit and the drilled formation. The optimal loading parameters are identified in this work based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
47
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 112 publications
(48 citation statements)
references
References 28 publications
1
47
0
Order By: Relevance
“…Driven by external harmonic excitations, these implementations are capable of motions such as rectilinear [23,24] unidirectional [25] and bidirectional [24] by utilizing a periodically driven mass/inertia that interacts with the main robot body. A three-masses model was analysed and compared with a low dimensional model in [26]. More interestingly, the authors considered several system control parameters including the applied static force, the amplitude and frequency of the applied force, which were optimally chosen through the higher dimensional model simulations.…”
Section: Introductionmentioning
confidence: 99%
“…Driven by external harmonic excitations, these implementations are capable of motions such as rectilinear [23,24] unidirectional [25] and bidirectional [24] by utilizing a periodically driven mass/inertia that interacts with the main robot body. A three-masses model was analysed and compared with a low dimensional model in [26]. More interestingly, the authors considered several system control parameters including the applied static force, the amplitude and frequency of the applied force, which were optimally chosen through the higher dimensional model simulations.…”
Section: Introductionmentioning
confidence: 99%
“…eir investigations showed that ultrahigh-frequency axial vibration can significantly enhance drilling rates compared to the traditional rotary-type method [12]. Pavlovskaia et al [13] concluded that a low-dimensional model provides good estimates for the optimal static force and the amplitude of the dynamic force and that this model can be used for the operational control of the drilling system, with the loading parameters being adjusted to achieve a resonant situation while drilling through different formations. Zhao [14] developed a simple nonlinear 2-DOFs (degrees of freedom) mass-spring model that can be used to analyze the process of dynamic cutting with normal ultrasonic vibration excitation.…”
Section: Introductionmentioning
confidence: 99%
“…Aspects of static force, amplitude and frequency were considered in Refs. [16,17]. by Ekaterina Pavlovskaia and his co-authors, and two selected models of vibro-impacting drilling system were also compared in these papers.…”
Section: Introductionmentioning
confidence: 99%